1980
DOI: 10.2172/5303299
|View full text |Cite
|
Sign up to set email alerts
|

Environmental monitoring at the Lawrence Livermore Laboratory. 1979 annual report

Abstract: described herein are sample collection and analysis proceduros employed in p-ironmental monitoring at the Lawrence Livermore Laboratory. An inte al part of the quality assurance program developed £or environmental monI ring at Livermore, these procedures provide a basis for verifying that sarvp' nq and analytical activities are being performed as specified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Further exploration of the Z-pinch in which magnetic fields in the megagauss range can be produced, indicated that some enhancement of stability could be possible due to finite ion Larmor radius effects, e.g. Bayley et al, [131] Struve [132], Davies et al [14], or finite resistivity, e.g. Culverwell et al [133], Cochran and Robson [134]: or sheared axial flow, e.g.…”
Section: Regimes For Stability Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploration of the Z-pinch in which magnetic fields in the megagauss range can be produced, indicated that some enhancement of stability could be possible due to finite ion Larmor radius effects, e.g. Bayley et al, [131] Struve [132], Davies et al [14], or finite resistivity, e.g. Culverwell et al [133], Cochran and Robson [134]: or sheared axial flow, e.g.…”
Section: Regimes For Stability Modelsmentioning
confidence: 99%
“…Experiments on the compressional pinch have indicated a reduction in growth rate under large Larmor radius conditions [131,132,182] but it is difficult to be more precise because of the time limitations of the experiments. Compression Z-pinch experiments can be devised such that at first compression i τ i is larger than 1 and a i /a is optimal at ∼0.1 [183].…”
Section: Large Ion Larmor Radius (Llr) Effectsmentioning
confidence: 99%
“…LLNL's first use of these dose-rate formulas in our environmental annual reports is described by Silver et al (1980).…”
Section: Ground Watermentioning
confidence: 99%
“…Beginning in 1975, quarterly samples were obtained from the drainage ditch at the northwest corner of the site and analyzed for pesticides (Silver et al 1976). This monitoring program continued unchanged for a number of years (Silver et al 1977, Silver et al 1978, Silver et al, 1979, Silver et al 1980, Toy et al 1981, with quantitative results for pesticide monitoring first being published in 1978. Beginning in 1981, storm water samples were also analyzed for gross alpha, gross beta, and tritium (Auyong, Griggs, and Buddemeir 1982).…”
Section: Storm Water Runoff Monitoringmentioning
confidence: 99%